Espaço ecomorfológico da fauna de quirópteros da região do Alto Tocantins, GO: uma perspectiva através da análise da morfologia alar - Oliveira, Edney Rocha de (2000)
This study was conducted in the Alto Tocantins Region (between 13° 45' - 14º 35' S and 47º50' - 49º 15' W; State of Goiás, Brazil) about 220 km NNE of Brasília in the biome of Cerrado. Four assemblages of bats from the Alto Tocantins Region were studied. Aspect-ratio (shape of the wing) and wingloading (body mass and wing size relationship) components were examined by Factor Analysis. The distances between the taxa were calculated by Euclidean distance and by the Pearson's product moment correlation coefficient. The resulting matrix were summarized in dendrograms performed by the UPGMA (unweighted pair-group method using arithmetic averages) clustering method. The distribution of the centroids of the species on the Factor Analysis axis are rigth-skewed, with the majority of taxa located toward center tand suggesting that the bat assemblages features of the Cerrado is characterized by small insectivores and frugivorous with high ar moderate wing loading. Forest formations (gallery forests and dry forests) seem to play a crucial role in the definition of the bat assemblage features. Such habitat types represent mesic conditions contrasting with the open areas.